2021
DOI: 10.1177/15353702211035693
|View full text |Cite
|
Sign up to set email alerts
|

E2F3 drives the epithelial-to-mesenchymal transition, cell invasion, and metastasis in breast cancer

Abstract: E2F3 is a transcription factor that may initiate tumorigenesis if overexpressed. Previously, we demonstrated that E2F3 mRNA is overexpressed in breast cancer and that E2F3 overexpression results in centrosome amplification and unregulated mitosis, which can promote aneuploidy and chromosome instability to initiate and sustain tumors. Further, we demonstrated that E2F3 leads to overexpression of the mitotic regulator Shugoshin-1, which until recently had unknown roles in cancer. This study aims to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
(55 reference statements)
0
30
0
Order By: Relevance
“…To further explore the downstream genes of the LINC00958/IGF2BP3 axis in EC, we combined RNA sequencing results and genes coexpressed with IGF2BP3 from the TCGA database and discovered that E2F3 was the downstream effector. E2F3, as a member of a small family of transcription factors, is involved in the tumorigenesis of many malignancies [ 42 – 44 ]. Some studies have identified E2F3 as an oncogene that promotes the progression of EC [ 24 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the downstream genes of the LINC00958/IGF2BP3 axis in EC, we combined RNA sequencing results and genes coexpressed with IGF2BP3 from the TCGA database and discovered that E2F3 was the downstream effector. E2F3, as a member of a small family of transcription factors, is involved in the tumorigenesis of many malignancies [ 42 – 44 ]. Some studies have identified E2F3 as an oncogene that promotes the progression of EC [ 24 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CDK2 has also been reported to be associated with growth inhibition in TNBC bearing mice [ 89 ] and reduced cell migration in TNBC cell lines [ 90 ]. E2F3 has been reported to be associated with doxorubicin responses [ 91 ] and EMT mechanisms in TNBC [ 92 ]. MCM2 and MCM3 have also been reported to have a role in DNA repair mechanisms in breast cancer [ 93 ], and these genes have also been reported as predictors of other NAC response predictive models [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, E2F3 expression has been consistently associated with proliferation, metastasis and drug resistance of many malignancies. [43][44][45][46][47][48] In NB, early evidence of the potential involvement of E2F3 in oncogenesis was provided by an in vitro study, which demonstrated that E2F3 binds the proximal MYCN promoter in NB cell lines expressing MYCN, 21 indicating that E2F3 is critical for the full activation of MYCN. 49 Consistently with this finding, our study showed a strong association between MYCN amplification and E2F3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the transcription factors E2Fs are frequently deregulated in human cancers. In particular, E2F3 expression has been consistently associated with proliferation, metastasis and drug resistance of many malignancies 43–48 …”
Section: Discussionmentioning
confidence: 99%